Global burden of prostate cancer: age-period-cohort analysis from 1990 to 2021 and projections until 2040 - Feifan Chu; Lumin Chen; Qing Guan; Zujie Chen; Qiwei Ji; Yuning Ma; Jinzhong Ji; Mingxin Sun; Tingyang Huang; Haihan Song; Hao Zhou; Xiuquan Lin; et al. (World Journal of Surgical Oncology)
Abstract Background Prostate cancer (PCa) is the second most common cancer among men worldwide. This study uses data from the 2021 Global Burden of Disease (GBD) study to estimate the global burden of prostate cancer from 1990 to 2021. Methods We analyzed the incidence, mortality, and disability-adjusted life years (DALYs) of prostate cancer globally from 1990 to 2021. Based on the Sociodemographic Index (SDI), we used the estimated annual percentage change (EAPC) and Age-Period-Cohort model to compare the burden of disease across different age groups and regions with varying levels of development. Finally, we used the Bayesian Age-Period-Cohort model to predict the trend of changes in the disease burden of prostate cancer by 2040. Results In 2021, the global age-standardized incidence rate (ASIR) of prostate cancer was 15.37 per 100,000, an increase from 13.69 per 100,000 in 1990. However, the age-standardized mortality rate (5.26 per 100,000) and DALY rate (95.94 per 100,000) decreased significantly compared to 1990. The burden of prostate cancer increased with age, but overall, the burden across all age groups was lower in 2021 than in 1990. The only exception was the incidence rate among individuals under 75 in 2021. High-income regions such as North America and Australia exhibited the highest burden in terms of ASIR, though there has been some reduction in recent years. Conversely, the burden of mortality and DALYs was highest in regions such as sub-Saharan Africa, West Africa, and the Caribbean, where rates have continued to rise. Correlation analysis between SDI and the EAPC of the disease burden showed a negative correlation between EAPC of prostate cancer mortality and DALYs with SDI. The APC analysis showed that in 2021, the ASIR of prostate cancer in high SDI regions was still significantly higher across all age groups compared to other regions. In regions with middle SDI and above, the age-standardized mortality rate and DALY rate decreased over time or across birth cohorts, with a faster decline in areas with higher SDI. By 2040, it is projected that the global ASIR of prostate cancer will reverse its current trend and increase, while the age-standardized mortality rate and DALY rate will continue to decline, and the counts of incidence, mortality, and DALYs will keep rising. Conclusion Although the global mortality rate and DALY rate for prostate cancer show a decreasing trend, the number of new cases, deaths, and DALYs continues to rise due to global population growth and the aging population, and the disease burden remains significant. Furthermore, there are substantial geographic disparities in the disease burden of prostate cancer. Therefore, targeted programs should be implemented to strengthen prostate cancer diagnosis and treatment in these specific regions.